Surface Functionalization for Synergistic Catalysis: Silica–Alumina‐Supported Cationic Indium and Organic Base for Cyanoethoxycarbonylation. Issue 7 (15th April 2014) - Motokura, Ken; Ito, Yasuhiro; Noda, Hiroto; Miyaji, Akimitsu; Yamaguchi, Sho; Baba, Toshihide
Abstract A silica–alumina (SiO2–Al2O3) surface possessing both In3+ cations and an amine base has been prepared. Surface‐functionalized SiO2–Al2O3 was characterized by solid‐state 29Si MAS, 13C CP/MAS, and 27Al 2D MQ/MAS NMR spectroscopy; X‐ray photoelectron spectroscopy; and elemental analysis. The bifunctional surface demonstrates synergistic catalysis for cyanoethoxycarbonylation of aldehyde.